BARONGAN JOGO ROGO DALAM TRADISI SELAPAN DINO - Efendi, Junarto; Kusumastuti, Eny (Universitas Negeri Semarang, 2013)
The ceremony selapan dino is traditional ceremonies exercised regularly by villagers Gabus Pati starch every friday night wag e. Friday wage was a day of being believable villagers Gabus as days of difficult to obtain rejeki, so we needed held a ceremony selapan dino which aims to launch rejeki. The ceremony selapan dino to be held every 35 days, by villagers Gabus. The ceremony selapan dino in an hereditary manner alw ays performing barongan jogo rogo as requirement of the organizing of ceremonies selapan dino. The subjects in research is: how do you study textual and contextual the art of barongan jogo rogo in the tradition of selapan dino in the village of Gabus Pati starch. Textual study focused on the form of a show barongan jogo rogo in selapan dino, the study of contextual focused on function barongan jogo rogo in selapan dino. A me thod of research used in this research using methods qualitative. The technique of collecting data covering the technique of observation, the technique of interviews and engineering documentation. Engineering analysis of data in research is the reduction of data, presentation of data and the wi thdrawal of the conclusion. Research revealed that the art of barongan jogo rogo in the village of Gabus Pati starch appear around 1980 which was initiated by the father who was. Textual study art barongan jogo rogo in selapan dino focused on form consisting of a theme, a performer ( inv estors ), accompaniment ( vote ) place stage, motion, a way ( fashion, dressing, the property and the offerings ) and the audience. An art form barongan jogo rogo in selapan dino different with a gig barongan jogo rogo served as a whole. Barongan jogo rogo in the tradition of selapa n dino served in the form of mobile convoy village of Gabus. Study contextual the art of barongan jogo rogo in selapan dino can be known that baro ngan jogo rogo serves as a means of a ritual. The function of a ritual namely as a means of turning balah and ruwatan.A form of turning balah villagers Gabus namely by giving wisit to barongan one goes home, while the aim of turning balah to villagers Gabus escape from calamity misfortune; distress and obstruction. A form of ruwatan villagers Gabus namely mengarak barongan roving village as figures of protector of villagers Gabus. Suggestions in this research are villagers Gabus must remain hold staging barongan jogo rogo on tradition selapan dino as a form of love tow ards art barongan and efforts to the preservation of culture. Culture and tourism agency should be more can promote tradition selapan dino to other region via the internet, salebaran or newspapers so that tradition selapan dino can known to the territory of another